José Pereira Arouca, um construtor na Mariana Setecentista: entre arrematações, monopólios e redes de sociabilidades (1753-1800) - Monica Maria Lopes Lage (2018)
This thesis aims to study the life and works of one of the most important constructors that circulated by the Captaincy of Minas Gerais in the second half of the 18th century, José Pereira Arouca. He was Portuguese and came to America in a period of great social and urban transformations that the mining cities lived. Despite the fall of gold, the accumulation of riches provided by the golden age of extraction had contributed to the emergence of a wealthy colonial elite, and this elite financed the development of newly created cities. José Pereira Arouca settled in Mariana, in a moment of cultural and artistic effervescence, since the city had become the seat of the first bishopric of Minas Gerais. In this way, there was a lot of work opportunity, because the government, religious associations and residents worked hard for Mariana to present an aspect consistent with her new social condition. There was an outbreak of construction and many craftsmen were enriched in this period, especially the Portuguese. José Pereira Arouca became the largest builder of the city, and perhaps one of the richest men in all of Minas Gerais during this period. With the intention of discovering its history, this thesis proposes to carry out an intense documentary, bibliographical and iconographic research of his works. This methodology, that enable to understand José Pereira Arouca's life and career in the Minas Gerais State, allowed to raise the "corpus" of his work and analyze how it was interpreted by the colonial historiography of Minas Gerais.